Species diversity of herpetofauna in bat cave area, indarung village, lubuk kilangan district, padang city - Reza Sapitri; Fitra Arya Dwi Nugraha; Abdul Razak; Yusni Atifah (Jurnal Biologi Tropis, 2023)
Bat Cave is a new tourist attraction located in Indarung Village, Lubuk Kilangan District, Padang City. Changes in habitat will affect the fauna in it, especially the herpetofauna, because herpetofauna is very sensitive to environmental changes. Herpetofauna research in this area has never been done. The research was conducted in December 2022, the observation method used was the transect method combined with the VES (Visual Encounter Survey). The purpose of this study was to determine the diversity of herpetofauna species in the Bat Cave area. Based on the research, nine types of herpetofauna were found, consisting of six types of amphibians and three types of reptiles. Total number of individuals obtained was 57 individuals. The most common type found was Limnonectes blythii, namely 23 individuals. In this study, one individual was found endemic to West Sumatra, namely Ichthyophis elongatus. Based on the research conducted, the diversity of herpetofauna species in the Bat Cave area is low.